Sustratos y tiempos de cosecha en el rendimiento del forraje verde hidropónico de la cebada - Curasma Ccente, James (2021)
The test was carried out on the grounds of the National University of Huancavelica, between the months of January and February 2019, with the objective of evaluating the substrates and harvest times in the performance of the FVH of barley. For this, 54 trays (25.5x35.5cm) were used, distributed in three treatments; T0 (Control treatment or without substrate), T1 (sawdust), T2 (Stipa ichu ground), 100ml of 0.5% urea was added to the trays with substrate (55g of 2 to 3mm of particle) and allowed to soak for 24 hours. The sowing density was 2.5kg / m2. Irrigation was done twice a day. It was harvested in three times (15, 19, 23 days), thus cutting a quadrant of 10x10cm / tray.The different harvest times did not show significantly (P> 0.05) changes in the biomass production (3.54, 3.51 and 3.69kg / m2 for 15, 19 and 23 days respectively), increasing significantly (P <0.05) the height of plant (8.11, 9.47 and 9.92cm for 15, 19 and 23 days respectively) and decreasing significantly evidenced (P <0.05) the production of dry material (14.89, 12.94 and 11.35% for 15, 19 and 23 days respectively).The use of substrates allows a greater production of biomass in green (3.34, 3.66 and 3.74 kg / m2 with T0, T1 and T2 respectively), percentage of dry matter (13.66, 11.79 and 13.73% with T0, T1 and T2 respectively) allowing at the same time plant height (8.50, 9.44 and 9.56cm with T0, T1 and T2 respectively) higher than the control. Thus, concluding that the use of substrates allows a greater production of biomass in green, percentage of dry matter allowing at the same time higher plant height than the control, in addition to obtaining a higher percentage of dry matter treating with stipa ichu as substrate and harvest times. they do not significantly influence the green biomass production.